STRATEGI PENGEMBANGAN SDM MAHASISWA D3 PRODI PERMESINAN KAPAL UNHAN RI DALAM MENGHADAPI ERA DIGITALISASI MARITIM - Hakim, Moh Lukman (Blueprint Journal, 2026)
This research is motivated by the increasing need for operational efficiency and workplace safety in the maritime sector, particularly on traditional fishing vessels that frequently face high risks at sea. The objective of this study is to develop an Internet of Things (IoT)-based safety monitoring and maintenance management system capable of monitoring vessel conditions in real time. The method used involves the design and testing of an IoT device consisting of a GPS module, MPU6050 sensor, Arduino Uno, and SIM808 GSM module to measure position, vessel inclination, temperature, and wind speed, with the collected data transmitted to a web-based monitoring server. The results show that the system is capable of detecting potential hazards such as excessive inclination, providing visual warnings, and automatically storing data for further analysis and documentation. In conclusion, the implementation of this IoT system has proven effective in improving navigation safety, supporting data-driven decision-making, and facilitating more efficient and sustainable vessel maintenance planning. The era of maritime digitalization requires vocational graduates in marine engineering to possess not only strong competencies in conventional mechanical aspects but also adaptability to digital technologies such as engine monitoring systems, maritime IoT, engine performance data analytics, and vessel cybersecurity. Therefore, this study also aims to analyze the current state of digital competencies among Diploma 3 Marine Engineering students at the Republic of Indonesia Defense University (UNHAN RI) and to formulate human resource development strategies aligned with industry needs in the modern maritime sector. A mixed-methods approach was employed, involving questionnaires administered to 12 students, interviews with lecturers and industry practitioners, and observations of the curriculum and laboratory facilities. The findings indicate that the students’ mechanical competencies fall into the “very good” category (average scores of 4.17–4.42), whereas their digital competencies remain very low (average scores of 1.25–1.67), far below industrial standards, which range from 4–5. The gap analysis shows a competency deficit of 2.3 to 3.7 points in the areas of IoT, digital monitoring, predictive maintenance, and data literacy. The main factors contributing to the low digital competencies include limited integration of digital technology into the curriculum, insufficient laboratory facilities, and a lack of data-driven engine practice. This study recommends four key strategies for human resource development: (1) modernization of the curriculum with a digital orientation, (2) enhancement of laboratory infrastructure and digital simulators, (3) digital competency training and certification, and (4) strengthened industry collaboration to support technology-based learning. By implementing these strategies, the Marine Engineering Study Program is expected to significantly improve students digital competencies and produce graduates who are ready to support digital transformation in the maritime and defense sectors.